Digital Transformation and Organizational Learning: Situated Perspectives on Becoming Digital in Architectural Design Practice - Gardner, Nicole (Frontiers in Built Environment, 2022)
The architecture, engineering, and construction (AEC) industry is negotiating a slow and fragmented shift towards digital transformation (DT). To identify the drivers and barriers to DT in the AEC industry, this article draws on organisational learning theory. More specifically, it investigates learning dynamics related to digital technology knowledge and skills development in organisations in the architecture sector. Adopting an empirical approach, the research has collected data through a series of semi structured interviews (n = 17) with employees from four large-scale architecture organisations in REMOVED FOR PEER REVIEW. The article conceptualises the interviewees’ experiences of engaging with digital technology knowledge and skills in their workplace along a learning loop continuum and in relation to modes of single-, double-, and triple-loop learning. It finds that organisations are primarily fostering modes of single-loop learning and potentially missing opportunities to innovate. The research highlights the hybrid, extensible, and platform-ised nature by which individuals ‘learn’ digital technologies and computational systems in the architecture workplace and identifies opportunities for intervention. The research demonstrates the utility of organisational learning as a method to rethink approaches to DT in the AEC industry.